Adenomyoepithelioma of breast (Journal of Pathology of Nepal, 2016)
Adenomyoepithelioma of breast is a rare, benign proliferative tumor formed of proliferation of myoepithelial cells surrounding small epithelium lined spaces. We present two cases of adenomyoepithelioma of the breast. The irst case was of a 23-years-old female with right breast lump and the second of a 41-year-old female with left breast lump. No patient had prior, coexistent carcinoma of either breast. None had any family history of breast cancer either. Excisional biopsy, Hematoxylin and Eosin staining and immunohistochemistry with S100 were performed. The pathological diagnosis was adenomyoepithelioma.